2022
DOI: 10.1007/s00167-022-06988-3
|View full text |Cite
|
Sign up to set email alerts
|

Posterior tibial tubercle measured by the sagittal TT-TG distance correlates with increased risk for patellofemoral chondral lesions

Abstract: Purpose To evaluate the variation in tibial tubercle sagittal alignment in patients with and without patellofemoral (PF) cartilage wear. Methods This was a single-centre, retrospective review of patients that underwent a cartilage restoration procedure for isolated PF cartilage wear from 2014 to 2020. Patients were matched in a 1:2 ratio for age, sex and BMI to partial meniscectomy patients as controls. The sagittal TT-TG (sTT-TG) distance was measured on preoperative axial T2 magnetic resonance imaging (MRI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We found that a more posterior tibial tubercle relative to trochlear groove was a risk factor for atraumatic medial patellar facet lesions, which is in line with previous investigations that demonstrated an increased risk for patellofemoral chondral lesions in patients with a more posterior tibial tubercle relative to the trochlear groove. 16,17 Given the high rates of patellofemoral osteoarthritis following the posteromedializing Hauser procedure, 4 a more posterior tibial tubercle relative to the trochlear groove may be associated with patellar overload, which could explain the preponderance for atraumatic medial patellar facet lesions in patients with a relatively posteriorized tibial tubercle. Although medial trochlear facet hypoplasia is associated with trochlear dysplasia, 8 and thus patellar instability, 9 the converse (medial trochlear facet hypertrophy) has not been described previously in the literature as a risk factor for medial patellar facet chondral lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that a more posterior tibial tubercle relative to trochlear groove was a risk factor for atraumatic medial patellar facet lesions, which is in line with previous investigations that demonstrated an increased risk for patellofemoral chondral lesions in patients with a more posterior tibial tubercle relative to the trochlear groove. 16,17 Given the high rates of patellofemoral osteoarthritis following the posteromedializing Hauser procedure, 4 a more posterior tibial tubercle relative to the trochlear groove may be associated with patellar overload, which could explain the preponderance for atraumatic medial patellar facet lesions in patients with a relatively posteriorized tibial tubercle. Although medial trochlear facet hypoplasia is associated with trochlear dysplasia, 8 and thus patellar instability, 9 the converse (medial trochlear facet hypertrophy) has not been described previously in the literature as a risk factor for medial patellar facet chondral lesions.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 17 Several recent studies have demonstrated that sagittal TT-TG distance (also referred to as tibial tubercle height) is a significant risk factor for the development of isolated atraumatic patellofemoral cartilage lesions. 16 , 17 , 27 These studies suggest that a more posterior position of the tibial tubercle relative to the trochlear groove may predispose patients to the development of patellofemoral cartilage lesions in the absence of trauma or instability.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) plays a major role in the early diagnosis of PF joint disorders [1, 6, 9, 22, 33, 51, 59]. Cartilage injuries are often present and it is thus a cornerstone to know how reliable and accurate it is for detecting and grading PF cartilage defects.…”
Section: Introductionmentioning
confidence: 99%